The Effectiveness Of Perineal Massage In Primigravida Pregnant Women On Perineal Rupture During Delivery At The Bilal Medika Clinic Serang City - Resi Galaupa; Husniah Husniah; Nurqalbi Sampara (International Journal of Health and Pharmaceutical (IJHP), 2022)
Perineal massage is a perineal massage technique that is carried out during pregnancy about 1-6 weeks before delivery. Objective: to determine the effectiveness of perineal massage in primigravida pregnant women against perineal rupture during delivery. Research Methods: quasi-experimental (quasi-experimental) using 40 samples of pregnant women in the third trimester. Collecting data using questionnaire sheets and respondent contract sheets. Data analysis was carried out using the Chi Square test. Research Results: From 40 samples of primiparous women who gave birth, more respondents in the experimental group did not experience perineal rupture, namely 17 (85%). Meanwhile, the control group respondents who experienced more tears were 16 (65%) and p-value = 0.000 (<0.05) with OR = 16.924. Conclusion: There is a significant relationship between perineal massage in primigravida pregnant women and perineal rupture during delivery at the Bilal Medika clinic in 2022.